Grain size of sediment cores from the Western Irish Sea Mud Belt, June 2022 - Muir, Hannah C; Evans, Claire (In: Muir, Hannah C; Reading, David G; Warwick, Phillip E; Peel, Kate; Evans, Claire (2025): Sediment core data (organic carbon, dry bulk density, grain size, radionuclide) from the Western Irish Sea Mud Belt June 2022 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.983345, 2025)
Particle size distributions were determined using a Malvern Mastersizer 3000 laser microgranulometer. Every other sample depth was analysed down to 40–45 cm (e.g. 0–2 cm, 4–6 cm, etc.). Samples were dispersed in a 1% Calgon solution (sodium hexametaphosphate) and sonicated for 10 minutes prior to analysis. Samples with particle diameters >2000 µm were sieved using a 1000 µm mesh prior to analysis, and the results from laser diffraction (volumetric) were scaled to the overall sample (mass) by assuming constant sediment density. Particle size classes were grouped as: clay (<3.9 μm), silt (3.9–62.5 μm), mud (<62.5 μm), and sand (62.5–2000 μm).
Keywords: Irish Sea; Sediment core